Analisis Return on Assets (ROA) dan Return on Equity (ROE) terhadap Harga Saham - Evatul Djannah; Roni; Maftukhin; Dwi Harini; Indah Dewi Mulyani (Journal of Accounting and Finance (JACFIN), 2019)
The development of the capital market that is as tight as possible has resulted in many companies seeking business capital by conducting Initial Public Offerings (IPOs) in the capital market. This turned out to be well captured by the Indonesian banking industry and even some Indonesian banks had good stock performance so that they were included in the Location Quotient 45 (LQ) stocks. There are many things that can affect stock prices so research is needed on factors that affect stock prices, especially banking. The data obtained using secondary data, with the number of samples used were 5 public companies that were included in banking stocks in LQ45 and the analysis used was descriptive analysis, classical hypothesis testing and multiple regression analysis using the SPSS program. The results of the analysis reveal that simultaneous Return on Assets (ROA), and Return on Equity (ROE) do not affect the stock price and both can explain changes in stock prices weakly. Partially ROA has no effect on stock price nor does ROE affect stock price